Healthy Organs Uptake on Baseline 18F-FDG PET/CT as an Alternative to Total Metabolic Tumor Volume to Predict Event-Free Survival in Classical Hodgkin's Lymphoma - Morland, David; Triumbari, Elizabeth Katherine Anna; Maiolo, Elena; Cuccaro, Annarosa; Treglia, Giorgio; Hohaus, Stefan; Annunziata, Salvatore (Frontiers in Medicine, 2022)
Purpose: Healthy organs uptake, including cerebellar and liver SUVs have been reported to be inversely correlated to total metabolic tumor volume (TMTV), a controversial predictor of event-free survival (EFS) in classical Hodgkin’s Lymphoma (cHL). The objective of this study was to estimate TMTV by using healthy organs SUV measurements and assess the performance of this new index (UF, Uptake Formula) to predict EFS in cHL. Methods: Patients with cHL were retrospectively included. SUV values and TMTV derived from baseline 18F-FDG PET/CT were harmonized using ComBat algorithm across PET/CT systems. UF was estimated using ANOVA analysis. Optimal thresholds of TMTV and UF were calculated and tested using Cox models. Results: 163 patients were included. Optimal UF model of TMTV included age, lymphoma maximum SUVmax, hepatic SUVmean and cerebellar SUVmax (R² 14.0% - p<0.001). UF > 236.8 was a significant predictor of EFS (HR: 2.458 [1.201-5.030], p = 0.01) and was not significantly different from TMTV > 271.0 (HR: 2.761 [1.183-5.140], p = 0.001). UF > 236.8 remained significant in a bivariate model including IPS score (p=0.02) and determined two populations with different EFS (63.7% vs 84.9%, p=0.01). Conclusion: The Uptake Formula, a new index including healthy organ SUV values, shows similar performance to TMTV in predicting EFS in Hodgkin's lymphoma. Validation cohorts will be needed to confirm this new prognostic parameter.